Cannabis policing in mid-twentieth century South Africa (Historia, 2021)
From 1922, cannabis was policed in South Africa as a "dangerous drug". At mid-century, the United Nations recorded South African cannabis seizures as accounting for more than half of the world's annual recorded totals. This article outlines some main trends in South African cannabis policing between the late 1920s and 1970. It uses quantitative data derived from historical police records to document the impact of a shift in policing strategy - from a focus on possession to a directed targeting of supply - following recommendations made in a 1952 governmental report. Analysis demonstrates how this policy change, along with other factors, impacted arrests and amounts of cannabis seized, by division and district. We situate statistical findings within South Africa's political landscape.
Keywords: Cannabis; dagga; drug control; race segregation; policing; South Africa